MJDs family members: Potential prognostic targets and immune-associated biomarkers in hepatocellular carcinoma - Zhou, Lei; Chen, Guojie; Liu, Tao; Liu, Xinyuan; Yang, Chengxiao; Jiang, Jianxin (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is one of the most common gastrointestinal malignancies, which is not easily detected in the early stage, has a high recurrence rate, and a very poor prognosis. Machado-Joseph domain-containing proteases (MJDs) have both promoting-cancer and suppressive-cancer effects in tumorigenesis. The immune-cell infiltration and tumor microenvironment play an essential role in HCC disease development, therapeutic reaction, and prognosis. However, the associations between the MJDs family members and immune cell infiltration and tumor microenvironment in HCC remain poorly known. Thus, we aimed to demonstrate the relationship between MJDs family and HCC. This study investigated the mRNA expression/DNA methylation, associated immune infiltration and functions of MJDs family members in HCC using cBioPortal, The Cancer Genome Atlas (TCGA), UALCAN, Human Protein Atlas (HPA), MethSurv, Tumor Immune Estimation Resource (TIMER)databases. The expression profiles, prognostic, clinicopathologic features, promoter methylation levels, correlated signal pathways, associated immune infiltration cells, and immune biomarkers of MJDs family members were assessed. We found that expression levels of ATXN3, JOSD1, and JOSD2 were dramatically grown in HCC tissues and cell lines, and were connected to histological grades, sample types, TP53 mutations, lymph node metastatic status, genders, and patient ages. These genes showed prognostic value on OS, DSS, OS, PFS, and RFS. Meanwhile, our results suggested that promotor methylation levels of the MJDs family were closely related to these family mRNA expression levels, clinicopathologic features, and prognostic values in HCC. Moreover, we also found that the MJDs genes family had significant correlations with CD4+ T cells, CD8+ T cells, B cells, neutrophils, macrophages, and DCs. Subsequently, MJDs family members’ expression indicated significant associations with the levels of several lymphocytes, immunomoinhibitors, immunomostimulators, chemokine, and chemokine receptors. In addition, the expression level of MJDs family members has significantly correlated with cancer marker-related pathways. In summary, our results indicated that the aberrant expression of the MJDs genes family in HCC played a critical character in clinical features, prognosis, tumor microenvironment, immune-related molecules, mutation, gene copy number, and promoter methylation levels. Thus, MJDs family members may provide potential emerging strategies for targeted therapies in HCC patients, as well as serve as new prognostic biomarkers.